Black Cumin (Nigella sativa) Against Mycobacterium tuberculosis Strain H37RV And MDR-TB - Mashuri Masri; Cut Muthiadin; Masita Masita; Tri Cahyanto; Lianah Lianah; Rusny Rusny; Siska Tridesianti (Elkawnie, 2021)
Abstract: Tuberculosis (TB) is a contagious infectious disease caused by Mycobacterium tuberculosis. 10 million people suffer from TB Every year. Although TB is a preventable and treatable disease, 1.5 million people die every year due to TB. Alternative treatments continue to be pursued, and treatment with the latest TB drugs that are continuously being encouraged. Black cumin (Nigella sativa) seed contains essential oils with active compounds such as thymohydroquinone, Oleoresins, flavonoids, alkaloids, saponins, tannins, and terpenoids that act as antibacterial drugs. This study aims to determine the sensitivity of  N. sativa seed extract in inhibiting the growth of  M. tuberculosis strain H37RV and MDR-TB (Multidrug Resistance-TB). This research using Microscopic-Observation and Drug-Susceptibility Assay (MODS) method. Extraction of N. sativa was carried out by the maceration method using 70% methanol as a solvent. The results showed that the M. tuberculosis strain H37RV and MDR-TB were sensitive to N. sativa extract at concentrations of 5 and 10% but resistant to N. sativa extract at concentrations of 1 and 3%.Abstrak: Tuberkulosis (TB) adalah penyakit menular yang disebabkan oleh Bakteri Mycobacterium tuberculosis. Penyakit ini menimbulkan dampak kematian yang cukup mengkhawatirkan.  Penyakit tersebut dapat dicegah dan diobati. Salah satu sumber pengobatannya menggunakan biji jintan hitam (Nigella sativa) yang mengandung minyak atsiri dengan senyawa aktif seperti timohidrokuinon, oleoresin, flavonoid, alkaloid, saponin, tanin, dan terpenoid yang berfungsi sebagai obat antibakteri. Penelitian ini bertujuan untuk mengetahui sensitivitas ekstrak biji N. sativa dalam menghambat pertumbuhan M. tuberculosis strain H37RV and MDR-TB (Multidrug-Resistance-TB). Penelitian ini menggunakan metode Microscopic-Observation and Drug-Susceptibility Assay (MODS). Ekstraksi N. sativa dilakukan dengan metode maserasi menggunakan pelarut metanol 70%. Hasil yang diperoleh menunjukkan bahwa bakteri M. tuberculosis strain H37RV dan TB-MDR, kedua  strain tsb sensitif terhadap ekstrak N. sativa konsentrasi 5 dan 10%,  tetapi resisten terhadap  ekstrak N. sativa konsentrasi 1 dan 3%.